2011
DOI: 10.5539/ass.v8n1p156
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Parenting Style and Academic Achievement among Iranian Adolescents in Sirjan

Abstract: The purpose of the present study was to determine the relationship between parenting styles and academic achievement among adolescents in Iran. The respondents were 382 high school adolescents (251 female and 131 male) in the age range of 15 to 18 years old from selected high schools in Iran. The instrument used to measure parenting style was the parenting style scale by Baumrind (1991). The result of the study indicated that authoritative parenting style has positive significant correlation with academic achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 15 publications
1
14
0
2
Order By: Relevance
“…This study supports Borak et al (2016), Dehyadegary et al (2012), Kashahu et al (2015), and Parsasirat et al (2013) studies who found out that democratic parents strongly predicted academic performance of their children in Albania, Bangladesh and Iran. However, Turner, Chandler, and Heffer (2009) revealed positive difference in academic performance among students of democratic parents and a negative difference among those of laissez-faire, and authoritarian parents.…”
Section: Perceived Parenting Styles and Academic Performancesupporting
confidence: 90%
See 1 more Smart Citation
“…This study supports Borak et al (2016), Dehyadegary et al (2012), Kashahu et al (2015), and Parsasirat et al (2013) studies who found out that democratic parents strongly predicted academic performance of their children in Albania, Bangladesh and Iran. However, Turner, Chandler, and Heffer (2009) revealed positive difference in academic performance among students of democratic parents and a negative difference among those of laissez-faire, and authoritarian parents.…”
Section: Perceived Parenting Styles and Academic Performancesupporting
confidence: 90%
“…For instance, among the Asian communities, Besharat, Azizi, and Poursharifi (2011);Borak, Kawser, Haque, and Sharmin (2016) ;Dehyadegary, Yaacob, Juhari, and Talib (2012) ;Parsasirat Montazeri, Yusooff, Subhi, and Nen (2013);and Zahed, Rezaee, Yazdani, Bagheri, and Nabeiei (2016) found that most adolescents raised under democratic parenting style have higher academic success than those from authoritarian and laissez-faire parenting styles while Ishak, Low, and Lau (2012), Kang andMoore (2011), andPong, Johnston, andChen (2010) stated that both democratic and authoritarian parenting styles influence students' academic performance. In Europe, Garcia and Gracia (2009) found significant differences in academic performance among Spaniard children from laissez-faire homes.…”
Section: Introductionmentioning
confidence: 99%
“…This style of parenting should result in positive outcomes, as research has emphasized the importance of having high levels of authoritative style, and low levels of permissive style (Maddahi, Javidi, Samadzahed, & Amini, 2012). The effects of an authoritarian style varied across cultures and contexts (Dehyadegary, Yaacob, Juhari, & Abu, 2012) and thus the preferred level of practicing an authoritarian style might not be clear. This is true especially in the context of comparing collectivistic and individualistic cultures (Hung, 2007;Kokkinos & Hatzinikolaou, 2011) where parenting styles may have different patterns of relationships with children's outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Dentro de la corriente principal de estudios de prácticas parentales asociadas al aprendizaje escolar de estudiantes que cursan la enseñanza básica, destacan aquellos que se desarrollan desde el modelo de estilos educativos parentales de Baumrind (1971) -posteriormente ajustado por Maccoby y Martin, 1983-(Dehyadegary, Yaacob, Juhari & Talib, 2012Di Giunta, Uribe Tirado & Araque Márquez, 2011;Domenech Rodríguez, Donovick & Crowley, 2009;Drummond & Stipek, 2004;Seginer, 2006), actualmente desarrollado por Cumsille, Martínez, Rodríguez y Darling (2014) en Chile, quienes contribuyen, además, con la validación de la Escala Parental Breve (EPB) para la medición de prácticas parentales en familias con hijos adolescentes. El estilo educativo se define aquí como "(…) el conjunto de actitudes que los padres comunican a sus hijos a través de las interacciones con ellos y que crean un clima en el cual los comportamientos de los padres son interpretados por los niños y adolescentes" (Cumsille et al, 2014, p. 1).…”
Section: Prácticas Parentales Y Las Diferencias En Resultados Escolarunclassified